Global Norms : Creation, Diffusion, and Limits - Martinsson, Johanna (World Bank, Washington, DC, 2017)
Norms in development are typically established at the global level to solve complex development challenges on the ground. These norms are standards of expected behavior about how things ought to be conducted and are deemed crucial for societies to flourish. Global norms, however, often fail to successfully diffuse to local contexts. The author intend to argue in this report that many initiatives are effective in putting norms on the global agenda, but few of these norms lead to transformational change on the ground because of cultural and political economy challenges that were not considered in the norm formation or in the advocacy campaign process. Nonetheless, there are lessons to consider that could lead to more successful outcomes. This report explores the journey of norms in development, from emergence to implementation. Specifically, it seeks to identify effective strategies for norms to take root and make part of the global and domestic agendas and limits. It also identifies challenges to the implementation of norms and some possible strategies and tools to overcome these challenges. The report draws from various global policy advocacy campaigns with a particular focus on governance; it also includes notable historic campaigns, such as Britain's antislavery campaign.